KEANEKARAGAMAN JENIS KUPU-KUPU PADA LIMA TIPE HUTAN DI AREAL PT. HUTAN KETAPANG INDUSTRI KALIMANTAN BARAT - Sinaga, Jogi Yoepi; Rifanjani, Slamet; Yani, Ahmad (Universitas Tanjungpura, 2019)
Butterflies are species of insect found in all types of habitats. Butterflies can be used as bio-indicators of environmental change because butterflies are very sensitive to biotic and abiotic factors. The aim of this study to obtain data the diversity of butterfly species in several habitat types in the PT.Hutan Ketapang Industri. This study used observation method with a sweeping that is using insect nets and researchers are free to explore the area randomly for a specified time. This research was conducted in 5 Habitats, kerangas forest, peat swamp, lowland dipterocarps, riparian and wetlands. Five forest types are selected based on the density and diversity of forest vegetation. The results found 14 species with a total of 316 individuals. Based on the calculation of species diversity index of butterflies in five locations of 2.54212, shows that the diversity is classified as moderate and has an abundance index value of 0.963289 indicates that the abundance is classified as high. Then obtained a value of species wealth index of 2.75651 is classified as moderate and has a value of dominance index of 0.0868651 indicates that there is no dominant typeKeywords:Â butterfly, diversity, indicator habitat, bioindicator